Two‐Terminal MoS2‐Based Retinomorphic Devices with Enhanced Synaptic Plasticity - Younghoon Lim; Taehun Kim; Jaesik Eom; Onsik Harm; Junsung Byeon; Jungmoon Lim; Juwon Lee; Sangyeon Pak; SeungNam Cha (Advanced Electronic Materials)
Abstract Neuromorphic visual systems mimicking biological retina functionalities are emerging as next‐generation retinomorphic devices for consolidating sensing and memorizing systems. In particular, monolayer MoS2 has been proposed as a promising material for retinomorphic devices due to their unique electrical and optical properties. Despite the advantages of MoS2 material, several limitations, such as PPC (persistent photoconductivity) or additional operating voltage, restrict the optimization of neuromorphic visual systems in MoS2‐based retinomorphic devices. Herein, the two‐terminal retinomorphic devices are reported featuring a tailored gating voltage range near zero and enhanced synaptic plasticity by providing another recombination route to suppress the PPC effect. Furthermore, pattern recognition results confirm that the retinomorphic devices effectively emulate the functions of the retina with a low device‐to‐device variation. This remarkable performance of MoS2‐based retinomorphic devices utilizing a functionalized substrate presents proposes an important pathway toward designing 2D materials‐based synaptic devices.